2019
DOI: 10.3920/cep190028
|View full text |Cite
|
Sign up to set email alerts
|

Surface EMG signal normalisation and filtering improves sensitivity of equine gait analysis

Abstract: Low-frequency noise attenuation and normalisation are fundamental signal processing (SP) methods for surface electromyography (sEMG), but are absent, or not consistently applied, in equine biomechanics. The purpose of this study was to examine the effect of different band-pass filtering and normalisation conventions on sensitivity for identifying differences in sEMG amplitude-related measures, calculated from leading (LdH) and trailing hindlimb (TrH) during canter, where between-limb differences in vertical lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 46 publications
(83 reference statements)
1
32
0
Order By: Relevance
“…sEMG signal amplitude is sensitive to several internal and external factors [49], so appropriate normalization techniques must be applied to reduce between and within-subject variation and to allow comparisons between subjects, muscles and trials [77,78]. In equine subjects, obtaining a maximum voluntary contraction (MVC) is not possible, but normalization to a submaximal RVC has been shown to improve sensitivity and accuracy of equine gait analysis [32]. In this study normalization to the maximum signal observed during canter permitted examination of the meaningful proportional change in muscle activity between the related activities of canter and jump.…”
Section: Study Limitations and Additional Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“…sEMG signal amplitude is sensitive to several internal and external factors [49], so appropriate normalization techniques must be applied to reduce between and within-subject variation and to allow comparisons between subjects, muscles and trials [77,78]. In equine subjects, obtaining a maximum voluntary contraction (MVC) is not possible, but normalization to a submaximal RVC has been shown to improve sensitivity and accuracy of equine gait analysis [32]. In this study normalization to the maximum signal observed during canter permitted examination of the meaningful proportional change in muscle activity between the related activities of canter and jump.…”
Section: Study Limitations and Additional Considerationsmentioning
confidence: 99%
“…Surface electromyography (sEMG) provides equine biomechanists with a non-invasive tool for quantifying superficial muscle activity. sEMG has been used to study equine muscle function during normal locomotion at walk, trot and canter [28][29][30][31][32][33][34][35], but only two known studies have evaluated muscle activity during jumping [36,37]. Unfortunately, a comparison of findings between these studies is confounded by methodological variation for sEMG signal detection and processing and differences in the jumping tasks studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We investigated task-related motor noise at the level of muscle activation by analyzing EMG variability of the four recorded muscles. First, EMGs were low-pass filtered at 40Hz [41]. Then, over the same interval of 1s (as for force), the CV of the EMG (CV-EMG) was computed trial-by-trial.…”
Section: Emg Analysis: Muscular Noisementioning
confidence: 99%
“…Further steps (repeated scrubbing or further hair removal) were taken prior to data collection if an unacceptable level of impedance was observed making it unlikely the electrode preparation and attachment imposed limitations in the current study. Another of these recommendations for best practice is to normalize the recorded amplitudes to the maximum value for that individual as raw amplitude can be highly variable and is influenced by the muscle under consideration, the individual, and the electrode placement (St. George et al, 2019; Valentin & Zsoldos, 2016). The gold standard for normalization is a maximal voluntary contraction, where maximum contraction is voluntarily sustained over a period of time.…”
Section: Discussionmentioning
confidence: 99%